Monitoring Coxiella burnetii Infection in Naturally Infected Dairy Sheep Flocks Throughout Four Lambing Seasons and Investigation of Viable Bacteria - Álvarez-Alonso, Raquel; Zendoia, Ion I.; Barandika, Jesús F.; Jado, Isabel; Hurtado, Ana; López, Ceferino M.; García-Pérez, Ana L. (Frontiers in Veterinary Science, 2020)
Progression of Coxiella burnetii infection in four naturally -infected sheep flocks, and in their farm environment, was monitored throughout four lambing seasons. Flocks with an active infection were selected based on the presence of C. burnetii DNA in bulk-tank milk (BTM) and a high seroprevalence in yearlings during the previous milking period (Spring 2015). During four consecutive lambing seasons (2015/16-2018/19), samples were collected within one week after each lambing period from animals (vaginal swabs, milk and feces from ewes and yearlings) and the environment (dust inside indoor sheep farm premises). BTM samples and aerosols (outdoors and indoors) were monthly collected between lambing and the end of milking. Real-time PCR analyses showed different trends in C. burnetii shedding in the flocks, with a general progressive decrease in bacterial shedding throughout the years, interrupted in three flocks by peaks of reinfection reactivation associated to with specific management practices. A significant relationship was found between C. burnetii fecal shedding and the bacterial burden detected in dust, whereas shedding by vaginal route affected the detection of C. burnetii in indoors aerosols. Three genotypes were identified; SNP8 (3 flocks, 52.9% of the samples), SNP1 (2 flocks, 44.8% samples), and SNP5 (1 flock, two environmental samples). C. burnetii viability in dust measured by culture in Vero cells was demonstrated in two of the flocks, even during the fourth lambing season. The results showed that infection can remain active for over 5 years if effective control and biosafety measures are not correctly implemented.